Frequency response of revenue meters in measured active energy - Novotny, Jan; Drapela, Jiri; Topolanek, David (2016 17th International Conference on Harmonics and Quality of Power (ICHQP), 2016)
The paper deals with the issue of response of electronic-based revenue meters during transmission of active energy (power) at harmonic frequencies of higher order. Basic principle of active power measurement which is formed by harmonic components is summarized and expected behaviour of the meters compared with the requirements of currently valid standards for electricity meters is discussed. Consequently, an experimental verification of the meters' response up to 3 kHz is performed and results from wide range of tests are presented. Based on those results, modification of revenue meters' verification procedure is proposed.